Design and Fabrication of a Novel Ultra Compact Microstrip Diplexer Using Interdigital and Spiral Cells - Yahya, Salah I.; Rezaei, Abbas (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
A dual-band bandpass-bandpass microstrip diplexer with very small size and good performance is designed in this work. The proposed diplexer has a novel structure which is introduced for the first time in this paper. In comparison with the previously reported diplexers, it occupies the most compact size of 0.002 λg2 (226.7 mm2), fabricated on 0.787 mm dielectric substrate height. The resonance frequencies of the presented diplexer are located at 0.76 GHz and 1.79 GHz making it suitable for the global system for mobile communications (GSM) applications. It has a wide flat channels with two fractional bandwidths (FBWs) of 41.1% and 50%. Another feature of the proposed diplexer is its ability to suppress the harmonics. It can attenuate the 1st to 7th harmonics. Moreover, it has low insertion losses and low group delays at both channels while the isolation and return losses are acceptable. Finally, the proposed diplexer is fabricated and measured to verify the simulation results, where a good agreement between the simulation and measurement results is obtained.